PENGEMBANGAN LKPD ELEKTRONIK BERBASIS KEMAMPUAN BERPIKIR KREATIF PADA MATERI KOLOID - Rahima Rahima; zona octarya (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2024)
This research was instigated with the lack of student involvement in the learning process because the conventional learning model use, monotonous teaching material, and the lack of training on the use of student creative thinking ability. This research aimed at developing creative thinking ability-based student electronic worksheet on Colloid lesson by using ADDIE development model and finding out validity level, practicality, and student response to the student electronic worksheet. It was Research and Development (R&D) with ADDIE development model consisting of 5 steps—analysis, design, development, implementation, and evaluation. But, in this research, only limited to the development step. Practicality test and student response was conducted to a Chemistry subject teacher and ten the eleventh-grade students of Natural Science B at State Islamic Senior High School 2 Kepulauan Meranti. The data obtained were analyzed by using quantitative and qualitative descriptive analysis techniques. Creative thinking ability-based student electronic worksheet on Colloid lesson was tested valid with the percentage 80% by media experts, it was very valid with the percentage 95.45% by material experts, practicality test score by teacher was 85.92% with very practical criterion, and student response percentage was 64.5% with practical category. However, it is hoped that an effectiveness test will be carried out to find out the media effectiveness in the future.